2016
DOI: 10.1038/srep19816
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule inhibitor of tropomyosin dissociates actin binding from tropomyosin-directed regulation of actin dynamics

Abstract: The tropomyosin family of proteins form end-to-end polymers along the actin filament. Tumour cells rely on specific tropomyosin-containing actin filament populations for growth and survival. To dissect out the role of tropomyosin in actin filament regulation we use the small molecule TR100 directed against the C terminus of the tropomyosin isoform Tpm3.1. TR100 nullifies the effect of Tpm3.1 on actin depolymerisation but surprisingly Tpm3.1 retains the capacity to bind F-actin in a cooperative manner. In vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 43 publications
(46 reference statements)
3
33
0
Order By: Relevance
“…Surprisingly, neither anti‐Tpm compound ATM‐1001 nor ATM‐4015 altered cellular morphologies, raising the question why the anticipated mesenchymal transition was not observed. The answer may be found in recent analyses which have revealed that while (TR100) perturbs Tpm3.1 regulated actin filament depolymerisation (Bonello et al, ), Tpm3.1 still associates with the actin filaments in the presence of the drug. This therefore may explain why anti‐Tpm3.1 drugs do not phenocopy all effects of genetic deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, neither anti‐Tpm compound ATM‐1001 nor ATM‐4015 altered cellular morphologies, raising the question why the anticipated mesenchymal transition was not observed. The answer may be found in recent analyses which have revealed that while (TR100) perturbs Tpm3.1 regulated actin filament depolymerisation (Bonello et al, ), Tpm3.1 still associates with the actin filaments in the presence of the drug. This therefore may explain why anti‐Tpm3.1 drugs do not phenocopy all effects of genetic deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human non-muscle cofilin 1, WT, and the phosphomimetic S3D were expressed and purified from E. coli as described for WT cofilin (4), and final concentrations were determined spec-troscopically (54). Recombinant human tropomyosin Tpm3.1 (55) was purified as described (56). A 1 mM phalloidin stock (Thermo Scientific) was prepared in methanol.…”
Section: Protein Expression Purification and Labelingmentioning
confidence: 99%
“…Myosin Va and Tpm3.1 are widely-expressed in cells and are implicated in disease states including metastatic cancer, melanoma and type 2 diabetes, though we do not yet know if they function together in cells (Alves et al, 2013;Bonello et al, 2016;Chen et al, 2012;Kee et al, 2015). The myosin and tropomyosin pairs were selected such that they form both physiologically-relevant (striated muscle myosin II/Tpm1.1, myoVa/Tpm3.1) and non-physiologically-relevant (striated muscle myosin II/Tpm3.1, myoVa/Tpm1.1) pairs.…”
mentioning
confidence: 99%